Therapeutic, Prophylactic, Untoward, and Contraceptive Effects of Combined Oral Contraceptives: Catholic Teaching, Natural Law, and the Principle of Double Effect When Deciding to Prescribe and Use. - Casey, Murray Joseph; Salzman, Todd A. (American Journal of Bioethics, 2014)
Combined oral contraceptives (COC) have been demonstrated to have significant benefits for the treatment and prevention of disease. These medications also are associated with untoward health effects, and they may be directly contraceptive. Prescribers and users must compare and weigh the intended beneficial health effects against foreseeable but unintended possible adverse effects in their decisions to prescribe and use. Additionally, those who intend to abide by Catholic teachings must consider prohibitions against contraception. Ethical judgments concerning both health benefits and contraception are approached in this essay through an overview of the therapeutic, prophylactic, untoward, and contraceptive effects of COC and discussion of magisterial and traditional Catholic teachings from natural law. Discerning through the principle of double effect, proportionate reason, and evidence gathered from the sciences, medical and moral conclusions are drawn that we believe to be fully compliant with good medicine and Catholic teaching.